Chemokine Expression in Human Oral Keratinocyte Cell Lines and Keratinized Mucosa - Bickel, M; Nothen, S M; Freiburghaus, K; Shire, D (Journal of dental research, 1996)
Chemoattractant cytokines regulate the immune response within the tissue by recruiting neutrophils and macrophages. These so-called chemokines include a large family of peptide molecules encoded by distinct genes. Their expression is controlled by a variety of microbial and host factors. Among host factors, interleukin-1 (IL-1) is thought to be a key regulator of tissue destruction and mediator of the local immune response. To study its influence on chemokine expression, we used a highly sensitive, semi-quantitative method to assess gene expression at the level of mRNA. RNA was extracted from human oral keratinocyte cell lines after treatment with recombinant human IL-1. To test the method further and possibly establish a chemokine mRNA expression pattern, we also extracted RNA from healthy oral keratinized mucosa. Purified RNA was reverse-transcribed and subsequently amplified in a polymerase chain reaction (RT-PCR) by means of specific primer pairs. Amplified sequences were analyzed by agarose gel electrophoresis, visualized by ethidium bromide staining, transferred to nylon membranes, and hybridized to biotinylated oligonucleotide probes. Detection was achieved by streptavidin-conjugated alkaline phosphatase, a chemiluminescent substrate, and autoradiography. Autoradiographs were analyzed by densitometric measurements. IL-1 stimulation resulted in an increase of the chemokine mRNAs encoding interleukin-8 (IL-8), monocyte chemoattractant protein-1 (MCP-1), and GROγ. Macrophage inflammatory protein-1α (MIP-1α) mRNA was not detectable in keratinocytes. In healthy oral mucosa, we found considerable variation between the subjects. Detection of chemokine mRNAs by RT-PCR proved to be sensitive, specific, and fast. It allows for the study of not only cell-line-derived RNA, but also of RNA isolated directly from biopsy material. The latter feature makes this method well-suited for diagnostic purposes.